3
$\begingroup$

State $B,C$, such that $B\begin{bmatrix} 1 & 2 \\ 4 & 8 \end{bmatrix}C=\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix}$

I tried some things, but I ended up with non invertible matrices, so I stopped for the moment.

Is there a quick way to guesswork here? (it's an assignment so, maybe some "nice" values for the entries will do)

I don't even know how I multiply a matrix to get 0-Entries with invertible matrices.

So maybe let's start at that part?

$\endgroup$
  • $\begingroup$ what can you say about the elements of a $2 \times 2$ invertible matrix? $\endgroup$ – user394255 Jan 6 '17 at 21:32
  • $\begingroup$ @A.Molendijk let the elements be a,b,c,d. Then $ad-bc\not=0$ $\endgroup$ – SAJW Jan 6 '17 at 21:33
  • $\begingroup$ nice. Are we allowed to use the fact that they are invertible or do we have to show by means of computation? $\endgroup$ – user394255 Jan 6 '17 at 21:37
  • $\begingroup$ @A.Molendijk it's explicitly staten those matrices are invertible, so I assume that. $\endgroup$ – SAJW Jan 6 '17 at 21:39
  • $\begingroup$ You could start with setting $B=\begin{pmatrix} b_1 & b_2 \\ b_3 & b_4 \end{pmatrix}$ and in the same way $C$. Then multiply the left hand side out and compare it with the right side. That would be the first thinge I'd try. $\endgroup$ – Fritz Jan 6 '17 at 21:42
7
$\begingroup$

Hint: row-reduce $\begin{bmatrix} 1 & 2 \\ 4 & 8 \end{bmatrix}$, then column-reduce. Row operations are equivalent to multiplication to the left by special invertible matrices (hence $B$) and column operations are equivalent to multiplication to the right (hence $C$).

More details: subtracting 4 times the first row from the second row is attained by $$\begin{bmatrix} 1 & 0 \\ -4 & 1 \end{bmatrix} \begin{bmatrix} 1 & 2 \\ 4 & 8 \end{bmatrix} = \begin{bmatrix} 1 & 2 \\ 0 & 0 \end{bmatrix}$$

Then subtracting twice the first column from the second column is attained by $$ \begin{bmatrix} 1 & 2 \\ 0 & 0 \end{bmatrix} \begin{bmatrix} 1 & -2 \\ 0 & 1 \end{bmatrix} = \begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix}$$

Added: This method works for matrices of any size. If $A$ is an $m\times n$ matrix of rank $r$, start with $$\begin{array}{cc} I_m & A \\ & I_n \end{array} $$ and row reduce $A$, performing the same row operations on $I_m$, to obtain $$\begin{array}{cc} B & \text{rref}(A) \\ & I_n \end{array}. $$

Then move the copy of $I_r$ to the top left corner and make zeroes everywhere else using column operations; again, perform the same column operations on $I_n$. When that is done one gets $$\begin{array}{cc} B & \begin{bmatrix} I_r & 0 \\ 0 & 0 \end{bmatrix} \\ & C \end{array}$$ and $$BAC = \begin{bmatrix} I_r & 0 \\ 0 & 0\end{bmatrix} .$$ The matrices $B$ and $C$ are not unique.

$\endgroup$
  • $\begingroup$ Far more elegant than my approach. $\endgroup$ – Doug M Jan 6 '17 at 21:51
  • $\begingroup$ This is probably what was intended in this exercise. OP would do well to remember that elementary transformations on rows/columns correspond to multiplication by elementary matrices. This is essential for matrix equivalence (rank), finding matrix inverse and solving linear systems. $\endgroup$ – Ennar Jan 6 '17 at 21:57
  • 1
    $\begingroup$ @DougM The OP is really computing the changes of basis that put the matrix in Smith normal form. $\endgroup$ – André 3000 Jan 6 '17 at 22:02
2
$\begingroup$

$B,C$ are not unique.

$\begin {bmatrix} 1&2\\4&8 \end{bmatrix} = B^{-1} \begin {bmatrix} 1&0\\0&0 \end{bmatrix}C^{-1}$

Suppose $B^{-1} = \begin {bmatrix} b_{11}&b_{12}\\b_{21}&b_{22} \end{bmatrix}$ and $C^{-1} = \begin {bmatrix} c_{11}&c_{12}\\c_{21}&c_{22} \end{bmatrix}$

$\begin {bmatrix} 1&2\\4&8 \end{bmatrix} = $$\begin {bmatrix} b_{11}&b_{12}\\b_{21}&b_{22} \end{bmatrix} \begin {bmatrix} 1&0\\0&0 \end{bmatrix}\begin {bmatrix} c_{11}&c_{12}\\c_{21}&c_{22}\end{bmatrix}\\ \begin {bmatrix} b_{11}&b_{12}\\b_{21}&b_{22} \end{bmatrix} \begin {bmatrix} c_{11}&c_{12}\\0&0 \end{bmatrix} \\ \begin {bmatrix} b_{11}c_{11}&b_{11}c_{12}\\b_{21}c_{11}&b_{21}c_{12} \end{bmatrix}$

$b_{11}c_{11} = 1\\ b_{11}c_{12}= 2\\ c_{12} = 2c_{11}\\ b_{21}c_{11} = 4b_{11}\\ $

Choose the other elements to make your calculation easy. i.e. $\det B^{-1} = 1$

$B = \begin {bmatrix} 1&0\\-4&1 \end{bmatrix}$

$C = \begin {bmatrix} 1&-2\\0&1 \end{bmatrix}$

Should work.

Completely different approach.

Daigonlize $\begin{bmatrix} 1&2\\4&8 \end{bmatrix}$

$P^{-1}\begin{bmatrix} 1&2\\4&8 \end{bmatrix}P = \begin{bmatrix} 9&0\\0&0 \end{bmatrix}$

$\frac 1{81}\begin{bmatrix} 1&2\\-4&1\end{bmatrix}\begin{bmatrix} 1&2\\4&8 \end{bmatrix}\begin{bmatrix} 1&-2\\4&1\end{bmatrix} = \begin{bmatrix} 1&0\\0&0 \end{bmatrix}$

$\endgroup$
2
$\begingroup$

I am surprised that no one has mentioned this: $$ B\pmatrix{1\\ 4}\pmatrix{1&2}C=B\pmatrix{1&2\\ 4&8}C=\pmatrix{1&0\\ 0&0}=\pmatrix{1\\ 0}\pmatrix{1&0}. $$ So, it suffices to find two invertible matrices $B$ and $C$ such that $B\pmatrix{1\\ 4}=\pmatrix{1\\ 0}$ and $\pmatrix{1&2}C=\pmatrix{1&0}$.

$\endgroup$
  • $\begingroup$ interesting! thanks $\endgroup$ – SAJW Jan 7 '17 at 16:04
2
$\begingroup$

The characteristic polynomial of the matrix $M=\begin{bmatrix}1&2\\4&8\end{bmatrix}$ is $\enspace\chi_N(\lambda)=\lambda^2-9\lambda$. Thus we have the following eigenvalues and eigenvectors: $$\lambda=9:\enspace e_1=\begin{bmatrix}1\\4\end{bmatrix} ,\qquad\lambda=0:\enspace e_2=\begin{bmatrix}2\\-1\end{bmatrix}.$$ In the basis $(e_1, e_2)$, with change of basis matrix $P=\begin{bmatrix}1&2\\4&-1\end{bmatrix}$, the matrix becomes $$P^{-1}MP=\begin{bmatrix}9&0\\0&0\end{bmatrix}.$$ Now pre-(or post-)multiply this matrix by the invertible $A=\begin{bmatrix}\frac19&0\\0&1\end{bmatrix}$. You obtain the relation $$(AP^{-1})MP=\begin{bmatrix}1&0\\0&0\end{bmatrix}$$ so that a solution is $B=AP^{-1}$, $\;C=P$. Another is $BP^{-1}$, $\;C=PA$.

$\endgroup$
1
$\begingroup$

We have that $$\begin {bmatrix} 1&2\\4&8 \end{bmatrix} = P \begin {bmatrix} 9&0\\0&0 \end{bmatrix}P^{-1} = (3P) \begin {bmatrix} 1&0\\0&0 \end{bmatrix} (3P^{-1}) $$ where $P \in \mathrm{Mat}_2(\mathbb{Q}).$

Thus, $$B\begin{bmatrix} 1 & 2 \\ 4 & 8 \end{bmatrix}C=\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix} \Longleftrightarrow (3BP)\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix}( 3P^{-1}C) =\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix}$$ or, $$(3BP)\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix} =\begin{bmatrix} 1 & 0 \\ 0 & 0 \end{bmatrix} (3P^{-1}C)^{-1}.$$ Then we obtain that $$3BP = \begin{bmatrix} a & b \\ 0 & c \end{bmatrix} ; (3P^{-1}C)^{-1} = \begin{bmatrix} a & 0 \\ d & e \end{bmatrix}$$ where $ b, d \in \mathbb{C}$ and $a,c,e \in \mathbb{C}^{*}$ (because $B, C$ are invertible). Then $$B = \frac{1}{3} \begin{bmatrix} a & b \\ 0 & c \end{bmatrix} P^{-1} ; \quad C= \frac{1}{3} P \begin{bmatrix} a & 0 \\ d & e \end{bmatrix}^{-1}; a,c,e \in \mathbb{C}^*; b, d \in \mathbb{C}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.